The Role of Religion in Written Language Maintenance and Shift in Uganda - Openjuru, George Ladaah (Multilingual Matters., 2019)
The primary focus of this chapter is the ambivalent role of religion in language maintenance and shift in Uganda. This chapter draws its theo-retical framework from the work of Pauwels (2005) on language mainte-nance and shift. Indeed, Pauwels’ contribution is central to this area and provides a very good definition of language maintenance and shifts in the context of language contact. Furthermore, she considers factors and forces promoting both language maintenance and shift, relevant to the case of Uganda and the Christian religion. Basically, according to Pauwels (2005), both phenomena of language maintenance (LM) and language shift (LS) come about in the context of language contact. An outcome of this process is that one language may give way to the other as the domi-nant language.The contact of significance in this Ugandan language landscape was between European Christian missionaries and native Africans in Uganda. The missionaries introduced two aspects of language use: literacy, which contributed to language maintenance, and formal school education, which promoted the use of English in favor of local languages. The Christian missionaries created two powerful social institutions in Uganda: school and church. These two social institutions produced the conflicting forces of both LM and LS in the Ugandan language landscape, as I shall show in this chapter. Language use in this chapter will be con-sidered largely in terms of the written text (literacy) and to some extent spoken language as well.Religion, language, literacy and education have always been associated in Africa to the same degree as in other parts of the world. The three noted ‘Religions of The Book’ are Islam, Christianity and Judaism (Kapitzke,1999). Accordingly, religion, especially the Christian religion, through the activities of its missionaries, has done a lot in spreading alphabetic literacy in Africa (Venezky, 1999) and has triggered both LM, through the development of orthographies and printing in local languages, and LS, through the introduction of school education based on the use of English as the language of instruction and power in Uganda. Before going into a detailed discussion, it is important to look at the language context in Uganda. I will draw on the literature and also refer briefly to my field notes.